Fiber reorientation in hybrid helicoidal composites. (October 2020) - Wang, Di; Zaheri, Alireza; Russell, Benjamin; Espinosa, Horacio; Zavattieri, Pablo
Abstract: Naturally occurring biological materials with stiff fibers embedded in a ductile matrix are commonly known to achieve excellent balance between stiffness, strength and ductility. In particular, biological composite materials with helicoidal architecture have been shown to exhibit enhanced damage tolerance and increased impact energy absorption. However, the role of fiber reorientation inside the flexible matrix of helicoid composites on their mechanical behaviors have not yet been extensively investigated. In the present work, we introduce a Discontinuous Fiber Helicoid (DFH) composite inspired by both the helicoid microstructure in the cuticle of mantis shrimp and the nacreous architecture of the red abalone shell. We employ 3D printed specimens, analytical models and finite element models to analyze and quantify in-plane fiber reorientation in helicoid architectures with different geometrical features. We also introduce additional architectures, i.e., single unidirectional lamina and mono-balanced architectures, for comparison purposes. Compared with associated mono-balanced architectures, helicoid architectures exhibit less fiber reorientation values and lower values of strain stiffening. The explanation for this difference is addressed in terms of the measured in-plane deformation, due to uniaxial tensile of the laminae, correlated to lamina misorientation with respect to the loading direction and lay-up sequence. Graphical abstract: Image 1 Highlights: A hybrid architecture, Discontinuous Fiber Helicoid (DFH) composite is designed. In-plane fiber reorientation in DFH is quantified numerically under uniaxial tensile. Compared with other architectures, DFH exhibits less fiber reorientation values. As opposed to other architectures, strain stiffening was not observed in DFH.